MOTIVASI MEMBUKA DESTINASI DESA WISATA DENGAN MEMANFAATKAN SUMBER DAYA ALAM - Danang Sunyoto; Tri Nur Rohmah; Iwan Budiherwanto (Bajang Institute, 2024)
Efforts to increase motivation to open tourist village destinations by utilizing natural resources. Problem: Business actors in the tourism village sector individually and/or in groups have not yet done their job optimally. Method/steps: Carry out the stages of opening a tourist village destination, namely; natural resource potential surveys, tourism feasibility studies, community participation, skills and knowledge development, tourism infrastructure development, promotion and marketing, environmental management, as well as ongoing evaluation and monitoring. Results: There is still a need to develop knowledge and skills and increase motivation to open tourist villages.